Increasing prevalence of Diphyllobothrium cestodes in seals from the North and Baltic Sea over 26 years - Striewe, Lotte Caecilia; Boyi, Joy Ometere; Pigeault, Rémi; Wohlsein, Peter; Siebert, Ursula; Lehnert, Kristina (Frontiers in Veterinary Science, 2025)
IntroductionHarbor seals (Phoca vitulina) and grey seals (Halichoerus grypus) are infected by trophically transmitted intestinal cestodes of the genus Diphyllobothrium. Diphyllobothrium species can cause zoonotic infections in humans when larval stages are ingested with undercooked fish products. Diphyllobothriid cestode prevalence, infection dynamics, and health impact in phocid seals around densely populated coastal areas are little understood, and their species delineation remains challenging.MethodsData collected between 1996 and 2021 within the stranding network of the federal state of Schleswig-Holstein, Germany, were used to analyze cestode prevalence and infection intensity in 1,317 harbor and 153 grey seals from the North Sea and Baltic Sea. A generalized additive model (GAM) assessed host-related factors and longitudinal effects on cestode prevalence in harbor seals from the North Sea (n = 1,284). The impact of cestode infections on host health was assessed using histopathological data from intestinal tissue samples. For molecular species identification, cestode DNA was amplified using mitochondrial cytochrome-C-oxidase subunit I (COI) and ribosomal internal-spacer-2 (ITS-2) markers.Results and discussionA highly significant increase in cestode prevalence over the 26-year study period was revealed in harbor seals from the North Sea, with prevalences of 0–14% between 1996 and 2012 and 9–36% from 2013 to 2021. Cestode prevalence in grey seals showed significant ecosystem-specific differences and was higher in the Baltic (64%) than in the North Sea (1%). Infection intensities were species-specific, and grey seals exhibited severe infections significantly more often than harbor seals. Histopathological alterations in intestinal tissue were unrelated to cestode infections. Molecular analyses showed that both pinniped species are infected with the same diphyllobothriid species, with the highest sequence similarities of 98.85% (ITS-2) and 90.65% (COI) to Diphyllobothrium schistochilos. Increasing cestode prevalence in harbor seals from the North Sea reflects ecosystem changes impacting host–parasite interactions. Clear species- and ecosystem-specific differences are related to differences in immunological traits and ecological conditions, such as the presence of prey species serving as intermediate hosts. Further research on conclusive species identification, health impact, intermediate hosts, and transmission pathways is necessary. The assessment of intermediate hosts and their population dynamics, especially contemplating the impact of environmental change, is crucial for evaluating zoonotic potential and comprehensively assessing the risk for humans.